Bioactivity of Argentinean essential oils against permethrin-resistant head lice, Pediculus humanus capitis - Toloza, Ariel Ceferino; Zygadlo, Julio Alberto; Biurrun, Fernando Noe; Rotman, Alicia; Picollo, Maria Ines (Entomological Society of America, 2019)
Infestation with the head louse, Pediculus humanus capitis De Geer (Phthiraptera: Pediculidae), is one of the most common parasitic infestation of humans worldwide. Traditionally, the main treatment for control of head lice is chemical control that is based in a wide variety of neurotoxic synthetic insecticides. The repeated overuse of these products has resulted in the selection of resistant populations of head lice. Thus, plant-derived insecticides, such as the essential oils seem to be good viable alternatives as some have low toxicity to mammals and are biodegradable. We determined the insecticidal activity of 25 essential oils belonging to several botanical families present in Argentina against permethrin-resistant head lice. Significant differences in fumigant activity against head lice were found among the essential oils from the native and exotic plant species. The most effective essential oils were Cinnamomum porphyrium, followed by Aloysia citriodora (chemotype 2) and Myrcianthes pseudomato, with KT 50values of 1.12, 3.02 and 4.09; respectively. The results indicate that these essential oils are effective and could be incorporated into pediculicide formulations to control head lice infestations once proper formulation and toxicological tests are performed.